Impact of the adoption of conservation practices on cereal consumption in a maize-based farming system in the Chinyanja Triangle, Southern Africa - Mango, Nelson; Makate, Clifton; Tamene, Lulseged D.; Mponela, Powell; Ndengu, Gift (Elsevier, 2020)
This study concerns the potential impact of the adoption of soil and water conservation technologies on household food security. Our analysis is based on a sample of 312 households in the Chinyanja Triangle using questionnaires. We use Propensity Score Matching to estimate treatment effects of adoption. Results show that the adoption of conservation technologies has significant impact on cereal consumption. The Average Treatment effect on the Treated, based on three matching algorithms, ranges from 222.18 to 320.95 kg of cereal consumed per year. The results imply that efforts to improve the adoption of these technologies could contribute to food security.